DsbA-L ameliorates renal aging and renal fibrosis by maintaining mitochondrial homeostasis - Yang Ming; Liu Yan; Luo Shi-lu; Liu Chong-bin; Jiang Na; Li Chen-rui; Zhao Hao; Han Ya-chun; Chen Wei; Li Li; Sun Lin (Acta Pharmacologica Sinica, 2024)
Renal fibrosis is the final pathological change in renal disease, and aging is closely related to renal fibrosis. Mitochondrial dysfunction has been reported to play an important role in aging, but the exact mechanism remains unclear. Disulfide-bond A oxidoreductase-like protein (DsbA-L) is mainly located in mitochondria and plays an important role in regulating mitochondrial function and endoplasmic reticulum (ER) stress. However, the role of DsbA-L in renal aging has not been reported. In this study, we showed a reduction in DsbA-L expression, the disruption of mitochondrial function and an increase in fibrosis in the kidneys of 12- and 24-month-old mice compared to young mice. Furthermore, the deterioration of mitochondrial dysfunction and fibrosis were observed in DsbA-L−/− mice with D-gal-induced accelerated aging. Transcriptome analysis revealed a decrease in Flt4 expression and inhibition of the PI3K-AKT signaling pathway in DsbA-L−/− mice compared to control mice. Accelerated renal aging could be alleviated by an AKT agonist (SC79) or a mitochondrial protector (MitoQ) in mice with D-gal-induced aging. In vitro, overexpression of DsbA-L in HK-2 cells restored the expression of Flt4, AKT pathway factors, SP1 and PGC-1α and alleviated mitochondrial damage and cell senescence. These beneficial effects were partially blocked by inhibiting Flt4. Finally, activating the AKT pathway or improving mitochondrial function with chemical reagents could alleviate cell senescence. Our results indicate that the DsbA-L/AKT/PGC-1α signaling pathway could be a therapeutic target for age-related renal fibrosis and is associated with mitochondrial dysfunction.